Proposta alternativa para análise do desempenho em provas cognitivas assistidas - Queiroz, Odoisa Antunes de (2010)
Since 1991, Brazilian researchers study the children’s learning potential, especially of children with special educational needs (SEN), based on supervised evaluation, in which the structured format (pretest -intervention –posttest) includes an intermediate step of a systematic help of the examiner, calculating the rate of gain between the initial step and the final, both without help. This analysis, however, has been criticized methodologically. This dissertation, then, analyzed alternative proposal for data analysis of assisted evidence, applied to data that were already collected of 248 children with (157) and without SEN (91) (average 8 years and six months old). In order for this to be done, data of 8 performed researches were integrated between 1999 and 2008, which utilized 4 assisted cognitive tests (270 handouts) and 3 psychometric tests (355 handouts). These data were organized in 3 studies, among them a theoretical one (Study 1), and they were analyzed regarding the: (a) relations between statusvariables (age, gender, levelof education, type of development problem –visual, communication or learning difficulties) and the cognitive performance in the assisted tests (b) performance in the two modalities of tests (psychometric and assisted) (Study 2); (c) performance in the steps without help (pretest) and of maintenance (posttest) of the assisted tests, by the Item Response Theory (IRT); (d) comparison of the traditional rate of gain and the obtained results by the IRT (Study 3). In the Study 2, the 6 researches already done were put together, providing an overview about the projects, with contributions, in an effort to verify some distinctions between the two evaluative modalities. In this study, the collected information showed that, in fact, the two methodologies have their peculiarities: the traditional ones evaluate questions regarding the examiner’s accumulated knowledge, while the assisted measure the learning potential. In what regards the comparisons of performance in the tests, it was verified that an inferior result in the psychometric test doesn’t lead the examined to a low cognitive gain in the assisted test. And still, the fact that an individual is suffering from a development problem doesn’t imply in his/her total failure in the tests. In the Study 3, the construction procedures of the data’s equalization of the assisted test showed that the pre and posttest’s steps have items with similar difficulty levels. In what is referred to the comparison between the traditional metrics and those obtained by the IRT, it was verified that the gain values and theta are similar. Finally, it is noteworthy that the two evaluation modalities, assisted and psychometric, have their particularities, being important for the development of adequate measures, which will offer improvementto the psychological, educational, affective and social conditions of the population.